In situ formation of molecular Ni-Fe active sites on heteroatom-doped graphene as a heterogeneous electrocatalyst toward oxygen evolution - Wang, Jiong (2018)
Molecularly well-defined Ni sites at heterogeneous interfaces were derived from the incorporation of Ni2+ ions into heteroatom-doped graphene. The molecular Ni sites on graphene were redox-active. However, they showed poor activity toward oxygen evolution reaction (OER) in KOH aqueous solution. We demonstrated for the first time that the presence of Fe3+ ions in the solution could bond at the vicinity of the Ni sites with a distance of 2.7 Å, generating molecularly sized and heterogeneous Ni-Fe sites anchored on doped graphene. These Ni-Fe sites exhibited markedly improved OER activity. The Pourbaix diagram confirmed the formation of the Ni-Fe sites and revealed that the Ni-Fe sites adsorbed HO− ions with a bridge geometry, which facilitated the OER electrocatalysis.